If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3.27x + 26.16 = 52.32 Reorder the terms: 26.16 + 3.27x = 52.32 Solving 26.16 + 3.27x = 52.32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26.16' to each side of the equation. 26.16 + -26.16 + 3.27x = 52.32 + -26.16 Combine like terms: 26.16 + -26.16 = 0.00 0.00 + 3.27x = 52.32 + -26.16 3.27x = 52.32 + -26.16 Combine like terms: 52.32 + -26.16 = 26.16 3.27x = 26.16 Divide each side by '3.27'. x = 8 Simplifying x = 8
| 3(p+2)=30 | | 10c+5=45 | | 3.52x+9=12.3904+3x | | w^2+12w+81=0 | | 35x-5y=7.7 | | |x-5|=3 | | 3x^2-5x+12x-20=0 | | -5y+8=8-5y-12 | | 15=3u | | x^3-5x+9x-45=0 | | 2z-4z=4 | | 11q+5=49 | | 2=2x+b | | -10y=-8x+14 | | 111111122222333366655444778*1212121212121212=9999999999999999999999999992 | | 543216845614845614564654d*54151561231651325445123141234=97812348521951215132156 | | 3(a-5)=40.8 | | X^2+32x+33=0 | | -3b-15=-24 | | 4=-p+2p | | 4=2c-9 | | 5e-7=21.5 | | 10x-6x=4 | | 30-.19m=26.58 | | 1x+6y=22 | | 11x-4=6x+11 | | 6t=1500 | | 3x-4(x^2-6x-7)=6(x-7) | | 0=x^3+x^2-2x | | 6x^7-5x^5+16x^4= | | 3x(4x+12x)=12x+36x | | 3t=5t |